Banking Efficiency and Financial Development in Sub-Saharan Africa - Kablan, Sandrine (IMF Working Papers; Working Paper ;, 2010)
This study assesses the determinants of banking system efficiency in sub-Saharan Africa (SSA) and asks what, besides the degree of efficiency, explains the low level of financial development in the region. It uses stochastic frontier analysis to measure efficiency and a generalized method of moments system to explain financial development. SSA banks are found to be generally cost-efficient, but nonperforming loans undermine efficiency, which suggests that improvement in the regulatory and credit environments should improve efficiency. The political and the economic environment have held back financial development in SSA.